Travel Pattern and Relaxation Activities Preference of the Visitors in Lego-Lego Makassar - Hajriyanti Yatmar; Muhammad Isran Ramli; Sakti Adji Adisasmita; Mubassirang Pasra (Future Science, 2022)
The analysis concept of transportation demand is using the trip and activity-based approach. Transportation planning is not only concerned about the trip demand of the commuters but also non-commuters such as leisure trips. Lego-Lego is one of the famous relaxation activity places in Makassar that support leisure trips. Lego-Lego is the only multipurpose relaxation facility provided by the government. Numerous people are visiting the Lego-Lego, especially in the weekend in the morning and afternoon. The long line of vehicles is often at the entrance and exit way of Lego-Lego due to the increase of visitors. The high demand to the place is important to overview the pattern of activities while use the facilities for expanding and developing the tourist area and reduce the traffic problems. According to the trip pattern and activities of visitors, this study aims to describes the visitors background, trip pattern and activities of people at Lego-Lego. This study used descriptive analysis and 1218 of total respondents. The result showed that the trip pattern of visitors using facilities as much as 88 patterns in the morning and 77 in the noon. Majority respondent’s pattern is “parking – rest area – parking” or about 17.08% in the morning and “parking – courtyard – rest area – parking” or about 13.87% in the noon. The trip pattern using facilities for morning and noon are quite different and low corellation. Hence, the corellation value shown 0,427 with not significantly affected the trip pattern and time period activities. In addition, the facilities with the most used were rest area and courtyard.